Alteração hidrotermal e geotermobarometria do Alvo Paz, Província Aurífera de Alta Floresta (MT), Cráton Amazônico - Martins, Henrique Bazzo [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The Alta Floresta Gold Province (AFGP), northern sector of the Mato Grosso State, corresponds to a crustal fragment of WNW-ENE direction, inserted into the southernmost portion of the Amazon Craton. It consists of paleoproterozoic plutonic, volcanic and vulcanosedimentary units generated into successive orogenic events onset, with calcium-alkaline magmatism and paleoproterozoic tectonic reworking with minor of Archean material. Its Several primary small gold deposits occur along the NW-SE Peru-Trairão belt. In this context, the primary mineralizations within the province can be clustered into four major groups: (1) disseminated Au ± Cu deposits; (2) vein-type Au ± Cu deposits; (3) vein-type Au ± Cu ± Mo deposits; and (4) vein-types Au + Zn + Pb ± Cu deposits. Despite the great metalogenetic and economic potential of the province, most studies have been focused in the descriptive and genetic models of mineralizations related to group (1). Although a significant number of deposits currently explored by prospector activity, the second group represent one of the least understood in the province. Thus, the main goal of this work is the characterization of the host-rocks, the hydrothermal alteration sequence, ore paragenesis and the mineral chemistry of white mica and chlorite of Alvo PAZ, inserted into the Peteca deposit region (Matupá, MT), which belong to the second-class deposits. Therefore, this work performed of conventional petrography, scanning electron microprobe and electron microprobe. In this way, the Alvo PAZ is majorly hosted by (1) medium-grained and isotropic to slightly anisotropic granitoid, locally intruded by (2) intermediate to acid subvulcanic. These lithotypes are variably affected by intense hydrothermal alterations, temporally represented by: (i) potassic with K-feldspar; (ii) sericitic; (iii) chloritic; (iv) epidotization; (v) silica injections and silicification, eminently in pervasive-styles, nevertheless...

A Província Aurífera de Alta Floresta (PAAF), setor norte do Estado de Mato Grosso, corresponde a um fragmento crustal de direção WNW-ENE, inserido no extremo sul do Cráton Amazônico. Constitui-se de unidades plutônicas, vulcânicas e vulcanossedimentares paleoproterozoicas derivadas de sucessivos eventos orogênicos, com magmatismo cálcio-alcalino, retrabalhamento de crosta paleoproterozoica com rara participação de material arqueano. Centenas de depósitos auríferos primários de pequeno porte, concentrados ao longo do cinturão Peru-Trairão, de direção NW-SE, ocorrem entre os municípios de Peixoto de Azevedo e Novo Mundo. Nesse cenário, quatro grupos de mineralizações podem ser individualizadas na província: (1) depósitos de Au ± Cu disseminados; (2) depósitos de Au ± Cu filonares; (3) depósitos de Au ± Cu ± Mo filonares; e (4) depósitos de Au + Zn + Pb ± Cu filonares. Apesar do grande potencial metalogenético e econômico que a PAAF apresenta, a grande maioria dos trabalhos na província tem centrado os modelos descritivos e genéticos das mineralizações relacionadas ao grupo (1). Embora com um número bastante significativo de depósitos atualmente explotados por atividade garimpeira, o segundo grupo corresponde a um dos menos compreendidos na província. Portanto, este trabalho tem por temática a caracterização das rochas hospedeiras, alteração hidrotermal, paragênese do minério e de química mineral da mica branca e clorita do Alvo PAZ, inserido no contexto do depósito Peteca (município de Matupá, MT), pertencente ao grupo (II). Para isso, esse trabalho se utilizou de petrografia em luz transmitida e refletida, microssonda eletrônica de varredura e microssonda eletrônica. Neste sentido, o Alvo PAZ ocorre hospedado basicamente em (1) granitoide de granulação média e ligeiramente anisotrópico, localmente truncado por (2) diques de rocha subvulcânica intermediária a ácida. Esses litotipos são...
Keywords: Depositos hidrotermais; Ouro; Crátons; Mineralogia; Geoquímica; Mica; Petrologia; Análise com microssonda; Microscopia eletrônica de varredura; Alta Floresta (MT)